Analisis Teori 4 Kaidah Atomic Habits Karya James Clear Sebagai Alternatif Model Penanaman Pendidikan Karakter di Tingkat SMA - Galang Dwi Aprilian; Fathi Hidayah; Jon Iskandar Bahari (Social Science Academic, 2026)
This study examines the persistent challenge of inconsistent character development in high school students, which leads to a "self-control separation" where positive behaviors diminish outside the school environment, contributing to social issues such as brawls and substance abuse. Existing literature on James Clear's Atomic Habits primarily focuses on internal discipline or younger age groups, leaving a significant gap in its application as a preventive behavioral shield against peer pressure for adolescents. Therefore, this research aims to reconstruct a new conceptual framework of the Atomic Habits model, specifically adapted as a proactive self-control mechanism for high school students to navigate peer pressure in non-formal settings. Employing a qualitative approach with a systematic literature review and conceptual analysis, the study primarily analyzes Clear’s Atomic Habits alongside relevant scientific articles and character pedagogy. Data analysis followed a thematic approach, involving comprehensive reading, systematic coding, and thematic connection to build a new conceptual model. Through an in-depth analysis of the primary source text of Atomic Habits by James Clear, the research reveals a reconstructed framework that shifts the focus from internal habit formation to an external, preventive behavioral shield. This model emphasizes the deconstruction of macro-character values into daily micro-habits, supported by choice architecture, enabling students to consciously design their environment and apply the four laws of behavior change (Make It Obvious, Make It Attractive, Make It Easy, Make It Satisfying) to resist peer pressure. This reconstructed framework offers a novel perspective on character education, empowering students with agency and self-control against external influences, thereby enriching the theoretical understanding of Atomic Habits in adolescent social resilience and providing practical guidance for educational interventions.